Optimizing Flexural Strength of Concrete Fc’ 14,5 MPa Using Acetylene Welding Carbide Waste - Bobby Damara; Sugeng Dwi Hartantyo (Kadiri University, 2021)
Replacing the main material using unused materials such as hazardous waste can be utilized in concrete innovation. One of the hazardous wastes that can utilize the waste generated from the acetylene welding process. The waste has hardening properties when exposed to water. Its properties are almost the same as cement can replace or add part of the cement mixture. Conducted this research was to determine the effect of using carbide waste from the acetylene welding process on the flexural strength of concrete. The experimental method is carried out by making test objects in the laboratory. The proportions of waste added were 7%, 10%, and 12% by weight of cement. The test object used is in the form of a beam with dimensions of 60 cm x 15 cm x 15 cm. The planned initial quality is concrete F'c 14.5 MPa (K175). The flexural strength test was carried out at the age of 27 days of concrete. From the results of the research carried out, it is found that the use of carbide waste from the acetylene welding process has not been able to improve the quality of concrete significantly. The highest flexural strength was obtained from waste at 7%, with a flexural strength value of 9.692 Mpa. So from these results, it can be used as a reference in the utilization of carbide waste from the acetylene welding process.